Which formula can be used to describe the sequence below?

27,9,3,1,1/3, ....

- an = -3an-1;a1=27

- an=1/3an-1;a1=27

- an=an-1-3;a1=27

- an=3an-1-1/3;a1=27

Respuesta :

Answer:

[tex]a_n[/tex] =[tex]\frac{1}{3}[/tex] [tex]a_n_-_1[/tex] ;    [tex]a_1[/tex] =27 is the correct equation

Step-by-step explanation:

For the sequence : 27,9,3,1,1/3, ....

Lets check all the given equations:

-> [tex]a_n[/tex] = -3[tex]a_n_-_1[/tex] ;   [tex]a_1[/tex] =27

[tex]a_2[/tex] = -3([tex]a_1[/tex] )= -3(27)=> -81  (this equation doesn't satisfy the sequence)

->[tex]a_n[/tex] =[tex]\frac{1}{3}[/tex] [tex]a_n_-_1[/tex] ;    [tex]a_1[/tex] =27

[tex]a_2[/tex] =[tex]\frac{1}{3}[/tex][tex]a_1[/tex] = [tex]\frac{1}{3}[/tex] (27) => 9

[tex]a_3[/tex] =[tex]\frac{1}{3}[/tex][tex]a_2[/tex] = [tex]\frac{1}{3}[/tex] (9) => 3 (this equation describe the sequence)

->[tex]a_n[/tex] =[tex]a_n_-_1[/tex] -3;    [tex]a_1[/tex] =27

[tex]a_2[/tex] =[tex]a_1[/tex] -3 = 27-3 => 24  (this equation doesn't satisfy the sequence)

-> [tex]a_n[/tex]  =3[tex]a_n_-_1[/tex] - [tex]\frac{1}{3}[/tex] ;     [tex]a_1[/tex] =27

[tex]a_2[/tex]  =3[tex]a_1[/tex] - [tex]\frac{1}{3}[/tex] = 3(27)- [tex]\frac{1}{3}[/tex] => 80.6 (this equation doesn't satisfy the sequence)